Opinions and award of the commissioners [electronic resource] : under the treaty of July 1, 1863, between Great Britain and the United States, for the final settlement of the claims of the Hudson's Bay and Puget Sound Agricultural Companies : pronounced, September 10, 1869. - British and American Joint Commission for the Final Settlement of the Claims of the Hudson's Bay and Puget's Sound Agricultural Companies.; Rose, John, Sir, 1820-1888.; Johnson, Alexander S. (Alexander Smith), 1817-1878. ([Montreal? : s.n.], 1869)
Electronic reproduction. Mode of access: Internet. 44